An Artistic and Archeological Study of Lakmah Mosque in the Village of Al-Ḥāql, Yāman, Rīmah Governorate – Yemen - Mohamed Ahmed Abd ElRahman ENAB (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
Lakmah Mosque, which is known as Aḥmad Hādī Al-Yāmani Mosque, is consid-ered one of the distinctive Yemeni mosques that reflects the shape of small cubical mosques in the Yemeni villages. This mosque is distinguished by its distinctive decorations and inscriptions. The research aims to shed light on the personality of the founder of the mosque, as he was one of the important individuals in the history of Rīmah governorate. In addition, the research sheds light on the mosque's style and design. The importance of the research lies in documenting this mosque, its artistic decorations, and its distinctive inscriptions recorded in the magnificent Ṯūluṯ script with its historical information and important cultural content. It also represents the publication for the first time of this mosque, which no one has studied before. The researcher followed the descriptive, analytical and inductive approach through several historical documents and endowment papers. The researcher reached several results, including knowledge of the date of the building of the mosque and knowing the founder's name, and his cultural and historical status, as he is considered one of the prominent political persons in the history of Rīmah governorate during the Ottoman era. The study also focused on the architectural style of the mosque and knowing its architectural origins. The researcher studied the wonderful inscriptions that decorate the ceiling of the mosque. These inscriptions provided us with much important historical information.